Financial Services for Developing Small-Scale Irrigation in Sub-Saharan Africa - Larson, Gunnar (World Bank, Washington, DC, 2012)
Food insecurity and income poverty are rampant in Sub-Saharan Africa. Thirty-one percent of children under the age of five are malnourished and some 72 percent of the population lives on less than US$2 day. Forty-one percent lives on less than US$1 day. The impoverished and hungry are concentrated disproportionately in rural areas and rely mainly on the consumption and sale of agricultural produce for their food and income. Africa has experienced increasing dependency on food imports that its countries cannot afford. Yet an estimated 700,000 hectares of arable land in Africa remains uncultivated. It is land that could become productive through small-scale irrigation using basic technology to draw on small-water resources, such as tube wells, and dambos. The technologies can be applied to cultivate smallholder plots of up to five hectares. Employing them will enable up to 4 million low-income households to intensify agricultural production and increase productivity. Small-scale irrigation can increase agricultural productivity and production, thus contributing to economic growth in rural areas and increased well-being among small holder farmers. Its potential to increase and stabilize food supply is especially important in light of the ongoing food crisis, and especially in Africa. Expanding the use of small-scale irrigation requires farmers to have access to financial services. The many constraints and obstacles that rural financial institutions in Africa confront must be purposefully navigated if financial services are to fulfill this role. Effectively tailoring financial services and products to support irrigation in different settings and among different client groups will be essential to success. Carefully targeting grant funding to the very poorest subsistence farmers and clearly separating it from lending will be likewise be critical to the sustainability of these financial services.